Protein-storing cells with 67 kDa protein in regularly tapped Hevea trees and in trees affected by tapping panel dryness - Tian Wei-Min; Hao Bing-Zhong (Journal of Rubber Research, 1999)
Protein-storing cells (PSCs) are found in secondary phloem of Hevea trees. In this study it was found that a 67 kDa protein based on SDS-PAGE might be the main component of the vacuole proteins in PSCs. SDS-PAGE analysis indicated that the 67 kDa protein varied in abundance at different levels of tree trunk in untapped and tapped trees, and that the protein also changed when tapped trees were affected by tapping panel disease (TPD). These changes were consistent with that of the amount of PSC vacuole proteins detectable by microscopy. The indirect immunocytochemistry in light microscopical level gave a more reliable evidence that the 67 kDa protein is quantitatively the more important component of the PSC vacuole inclusion. Latex exploitation caused a marked decrease in relative abundance of 67 kDa protein in the area under the tapping cut of the tree trunk. In comparison with healthy tapped trees, the trees which were affected by TPD and rested from tapping had much more 67 kDa protein in the bark tissues near the tapping cut. These facts indicate that the 67 kDa protein may be utilised as storage material for latex regeneration in the tapped trees and that the relatively abundant 67 kDa protein in TPD trees may be caused by resting the trees from latex exploitation.
Keywords: Tapping panel dryness